Pengembangan Kurikulum Kajian Islam (Islamic Studies) Untuk Penguatan Peran Perguruan Tinggi Dalam Pembaruan Islam di Indonesia - Sujadi .; Mahmud Arif; Sabarudin .; Nurul Hak (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2016)
Sunan Kalijaga State Islamic University and Indonesian Islamic University have paid great attention to the development of integrated-interconnected Islamic studies. Therefore, it is interesting to discuss models of their development epistemologically. In these universities, Islamic studies have been developed not only in faculties where Islamic studies are their concern but also in those focusing on the studies of secular knowledge. Islamic studies in the State Islamic University has been concerned on building epistemological foundations for its project of integrated-interconnected Islam whereas Islamic studies in the Indonesian Islamic University paid more attention to the Islamization, implemented science and scientific action. This model has led to different models for developing Islamic studies.